2018
DOI: 10.1093/ptj/pzy110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Signs and Symptoms of Axillary Web Syndrome and Breast Seroma During a Course of Physical Therapy 7 Months After Lumpectomy: A Case Report

Abstract: Background and Purpose Axillary web syndrome (AWS) and seroma are common and function-limiting side effects following treatments for breast cancer. Studies of AWS and seroma are rare, and there are no guidelines for physical therapy in these cases. Case Description After left breast lumpectomy due to invasive ductal carcinoma, a 65-year-old female patient underwent intraoperative radiation therapy and whole breast radiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Traumatic aspiration may increase the incidence of surgical site infection, clinic visit, and mental stress of patients [8]. While recent research supports that physical activity (PA) interventions can improve physical functioning, treatment-related symptoms, and QoL in cancer survivors [3,5,10,11], the possible effectiveness of PA in cases developing seroma has yet to be demonstrated [12]. Therefore, we herein evaluated for the first time the possible effects of a structured PA pathway for upper extremity recovery and QoL improvement in a case of peri-prosthetic seroma after BC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic aspiration may increase the incidence of surgical site infection, clinic visit, and mental stress of patients [8]. While recent research supports that physical activity (PA) interventions can improve physical functioning, treatment-related symptoms, and QoL in cancer survivors [3,5,10,11], the possible effectiveness of PA in cases developing seroma has yet to be demonstrated [12]. Therefore, we herein evaluated for the first time the possible effects of a structured PA pathway for upper extremity recovery and QoL improvement in a case of peri-prosthetic seroma after BC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, 11 studies were included in the present work [13,[31][32][33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included were two (18.2%) RCTs [31,32], one (9.1%) non-RCT [33], one (9.1%) retrospective observational study [34], and seven (63.6%) case reports [13,[35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found an association between vigorous PA performance and risk of developing AWS. The authors who previously examined risk factors for developing AWS found no relationship between training level and increased risk of AWS 47 , 48 , with the exception of a case report that described AWS development after physical effort 49 . Moreover, among the risk factors for the development of AWS should be considered younger age, greater time elapsed since surgery and number of resected lymph nodes 50 , but PA was not considered.…”
Section: Discussionmentioning
confidence: 99%